Charakterystyka statutu Uniwersytetu Papieskiego Jana Pawła II w Krakowie - Dyduch, Jan (Analecta Cracoviensia, 2012)
Foundation of the Pontifical University of John Paul II on 19 June 2009 required a new statute. It was adopted by the university senate on 23 February 2009 and handed over to Cardinal Zenon Grocholewski, the prefect of the Congregation for Catholic Education, on 26 May 2009. After entering the observations of the congregation by the Pontifical University of John Paul II in Cracow, it was approved by the congregation on 2 May 2010. The statute regulates the activity of the entire academic community and its individual faculties. It emphasizes evangelisation tasks of the university, its independence and autonomy to the civil authorities and compatibility of the canonical norms and the regulations of state for the universities.